DO OLDER TRANSNATIONAL MIGRANTS AGE WELL?. (11th November 2018) - Victor, C
Abstract: Ageing well remains a contested concept although there is broad consensus that it includes several key elements including material security, physical and mental health, psychological and social wellbeing. Do older people experiencing transnational migration demonstrate better (or worse) outcomes than older people in the country to which they migrated or in their country of origin. We use data from a survey of 830 older people (aged 50+) from 6 ethnic minority groups who migrated to Britain: African Caribbean, black African, Indian, Pakistani, Bangladeshi and Chinese and compare these wellbeing outcomes across migrant groups, with the British population and data for their countries of origin where available. Our data demonstrate ageing well outcomes vary across migrant groups. Across 3 parameters, life satisfaction, quality of life and self-rated health, migrants from Bangladesh demonstrate significantly lower outcomes compared with migrants from India (life satisfaction and quality of life) and the Caribbean (health rating).